Kłopoty pana sekretarza. Przyczynek do dziejów polskiej służby zagranicznej w dobie Sejmu Czteroletniego - Anusik, Zbigniew (Acta Universitatis Lodziensis. Folia Historica, 2001)
The article had been written about the activity of Józef Sierakowski, the Secretary of the Polish diplomatic mission in Stockholm 1789-1792. Disclosing the inner history of his nomination to the post of Secretary of the legation, the author at the same time discloses secret conditions, which manage to function of the Polish diplomatic service during The Great Diet. He points out Józef Sierakowski’s personal connections with Stanisław August’s environment and with the eminent members of The Foreign Affairs Deputation (Deputacja Interesów Zagranicznych). The most important part of the author’s narration is the case of long conflict between Sierakowski and the chief of the Polish diplomatic mission in Stockholm, the Starost of Tłumacz – Jerzy Potocki. When we analizę Jerzy Potocki’s correspondence, we could observe growing rows, aversion and acrimonious, which in short period of time changes into great hatred, which made it impossible for the Minister to communicate with Secretary of the legation. Except the conflict with Potocki, Sierakowski had also, in the same time, two more conflicts – with the management of the Swedish diplomatic service and with the majority of members of the Stockholm diplomatic corps. From the early days of June till the middle of December 1791, Józef Sierakowski had acted as chargé d'affaires ad interim, taking missing at this time in Sweden Jerzy Potocki’s place. To speak with conviction it was the most effective period of time in his all carieer an a diplomate. Sending to Warsaw plenty of interesting news, Sierakowski did not manage to avoid the Swedish discontent. He criticized Swedish king Gustavus III’s strokes against the revolutionary France and he published permanent reports from Stockholm (critical in relation to Gustavus III) in the „Gazette de Leyde”. When Potocki had arrived to Stockholm in the middle of December 1791, conflicts between two diplomats rised. During the period of last six months, which Sierakowski had spent in Sweden, Jerzy Potocki persistently managed to dismiss the Secretary from his office. But it was not an easy affair, because Sierakowski was on very good terms with the king (he was a trusted correspondent of the chief of his Cabinet) and with the Minister of Foreign Affairs in the Guard of Laws (Straż Praw) - Joachim Chreptowicz. Disappointed Potocki had been ready to vacate a post of Minister in Stockholm and tried to get permission to leave to Haga. Only in May 1792 the management of the Polish diplomatic service had decided to recall the conflicted and troublesome Secretary from Sweden. 30 June 1792 Józef Sierakowski left Stockholm at last. But the reminiscences of his conflict with Potocki appeared once more in August 1792 (when Sierakowski had decisively left the Polish diplomatic service), when he had calculated his dues from the Treasure of the Republic. Only at that time was ended the conflict, which for nearly two years had ruined the unity of the legation and had influenced the activity of the Polish mission in Stockholm negatively.